The first American grand prix : the Savannah Auto Races, 1908-1911 - Bailey, Tanya A., 1969- (McFarland & Co., 2014)
This book provides an in-depth look at the great motor races that took place in Savannah, Georgia, in the golden era of early road racing: the Grand Prize of the Automobile Club of America and the Vanderbilt Cup. By examining Savannah's earlier fame in national bicycle racing competitions and its ties to the powerful dynasties who controlled the racing world, the book explains how and why Savannah was chosen. It details the construction of the course, reveals why the races and course were considered ""America's greatest"" by international racing experts of the period and includes many biograph.